Az egészségbiztosítással kapcsolatos állampolgári preferenciák magyarázata - Janky, Béla; Kopasz, Marianna (Szociológiai Szemle, 2024)
The study examines the determinants of the individuals’ preferences on the welfare state. The focus is on the institutions of public health system, especially on the system of the health insurance. In the survey, carried out in April 1999, a referendum question format was adopted, thus the subjects had to choose between different institutional options, instead of valuing them separately. A simple model, built upon the notions of the rational choice theory, was tested with the help of regression techniques. The results indicate that the values on equality and the attitudes toward risk taking have significant effects on the respondents’ choices among the different alternatives. However, the hypotheses about the role of monetary self interest are not supported by the data. For a more sophisticated analysis, the explicit modeling of the utility function would be demanded.